Adsorption of three pesticides on polyethylene microplastics in aqueous solutions: Kinetics, isotherms, thermodynamics, and molecular dynamics simulation. (February 2021) - Li, Hui; Wang, Fenghe; Li, Jining; Deng, Shaopo; Zhang, Shengtian
Abstract: Microplastics could act as a carrier for pesticides in the water environment and pose a potential risk. This study mainly investigated the effects of reaction time, microplastics dosages, pH, and NaCl salinity on the adsorption characteristics of three pesticides (Imidacloprid, Buprofezin, Difenoconazole) on polyethylene (PE) microplastics in aqueous solution. The results showed that high pH and low NaCl salinity were conducive to the adsorption. The adsorption data were well fitted by the Freundlich isotherm model and the pseudo-first-order kinetics, indicating that it was mainly controlled by physical function. The adsorption capacity of three pesticides on PE microplastics followed the order of Difenoconazole > Buprofezin > Imidacloprid. The thermodynamic study indicated the adsorption of all pesticides as spontaneous and exothermic processes, and the elevated temperature was favorable to the adsorption. SEM-EDS and FTIR results verified that pesticides were adsorbed on the microplastics but the adsorption process was mainly controlled by intermolecular Van Der Waals Force and the microporous filling mechanism. Grand Canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulation results indicated that surface adsorption was the exclusive mechanism for the adsorption of pesticides on microplastics, and the final adsorption configurations revealed that there were complex interactions between the pesticide molecules and the C, H atoms in PE molecules. The results of this study illustrated that PE microplastics are potential carriers for pesticides in the water environment. Graphical abstract: Image 1 Highlights: Adsorption behavior and mechanism of pesticides on PE microplastics were investigated. Adsorption capacity followed the order of Difenoconazole > Buprofezin > Imidacloprid. High pH and low NaCl salinity were conducive to the pesticide adsorption. Adsorption was a spontaneous and endothermic process. Surface adsorption was the exclusive mechanism for the pesticide adsorption.